Clinical Teaching Effectiveness of Undergraduate Student Nurses in the United Arab Emirates - AlMekkawi, Mohamad (SAGE Open Nurs, 2020)
INTRODUCTION: Clinical supervision is a crucial aspect of developing nursing students' knowledge, skills, and professional attitudes. The characteristics of clinical instructors have a significant role in the progress and transition of students into their future professional roles. OBJECTIVE: The study aimed to examine the behaviors of effective clinical instructors as perceived by nursing students and faculty members in the UAE. METHODS: The study followed a cross-sectional quantitative research design to explore nursing students' and faculty members' perceptions of clinical instructors' effective behaviors that facilitate students' clinical practice. Data were collected from a convenience sample of 147 nursing students and 17 faculty members who completed an online version of the study survey at four nursing programs in the UAE. RESULTS: Students rated personality (M = 4.96, SD = 1.91) and teaching ability (M = 4.94, SD = 1.96) as the highest behaviors for effective clinical instructor. They perceived effective clinical instructor to be organized (M = 5.19, SD = 1.88), shows self-confidence (M = 5.16, SD = 1.84), able to answer questions (M = 5.16, SD = 1.90), emphasizes what is crucial to learn (M = 5.11, SD = 1.81), and takes responsibility for his/her actions (M = 5.11, SD = 1.90). While faculty members perceived effective clinical instructor to encourage a climate of mutual respect (M = 5.56, SD = 1.27), be approachable (M = 5.47, SD = 1.32), demonstrates clinical skill and judgment (M = 5.53, SD = 1.46), takes responsibility for his/her actions (M = 5.53, SD = 1.37), and be a good role model (M = 5.47, SD = 1.32). CONCLUSION: Understanding clinical instructors' effective behaviors and supporting them during students' clinical experiences inspire a productive teaching-learning environment that is crucial to improve students' motivation, expand their learning opportunities and improve their hands-on skills.